American college test assessment of educational hierarchies and scholastic survival at the University of the Philippines - Mercado, Aurea Adrias 1920- (s.n.], 1968)
This study aimed to ascertain if the American College Test (ACT), which is widely used for student assessment in American colleges and universities, can be used as a screening instrument at UP. The design utilized correlational and discriminatory techiniques for data involving academic factors, and computed chi-square test for data involving non-academic factors. Subjects of the study consisted of freshmen students who took the ACT on July, 1967 and were categorized based on their first semester grades at UP. It was concluded that the ACT scores are valid predictors of academic success. A student with a given high school grade and ACT score would get a certain freshmen grade; however, attention should be given to students who were academically successful but would not have been admitted on the basis of the ACT scores and vice versa